Membangun Minat Belajar Anak Usia Dini melalui Penggunaan Media Digital: Sebuah Refleksi Spiritualitas Pendidikan Kristiani - Simon Simaremare; Maythen Palyn (Sekolah Tinggi Teologia Kerusso Indonesia, 2024)
This article reviews the importance of Christian Education being taught to children as early as possible to improve children's faith education so that children have genuine and good faith in God. Introducing Christian education from an early age to students, it will increase students' spiritual potential. 21st-century education is characterized by the use of technology in learning as a requirement of the industrial era 4.0. Rapid and increasingly sophisticated technological advances have significantly changed human life in various fields. This research aims to identify the challenges and efforts experienced by Christian education in the digital era in instilling Christian teaching values in early childhood. This research uses the type of Library Research. The efforts made by Christian education in schools are to align education with current developments through technology-based learning media.